Pengaruh Self Efficacy, Self Esteem, Dan Employee Engagement Terhadap Kinerja Karyawan PT Usaha Utama Bersaudara Surabaya - Dwi Aji Pangestu; I Dewa Ketut Raka Ardiana (Manajemen Kreatif Jurnal, 2024)
This research aims to prove and analyze several things, such as the simultaneous and partial influence of Self-Efficacy, Self-Esteem, and Employee Engagement on Employee Performance at PT Usaha Utama Bersaudara Surabaya. This type of research is quantitative and all data is obtained through filling out a questionnaire distributed via Google Form. The sample in this study amounted to 66 people. The data analysis and hypothesis testing methods used are Validity Test, Reliability Test, Classic Assumption Test (normality test, multicollinearity test, and heteroscedasticity test), Coefficient of Determination Test (R2), Partial Test (t test), Simultaneous Test (f test) , and Multiple Linear Regression Coefficient Test. The results of data analysis and hypothesis testing using SPSS version 27. Where the results of this research show that partially Self Efficacy has a positive and significant effect on employee performance at PT Usaha Utama Bersaudara Surabaya, then partially Self Esteem has a positive and significant effect on employee performance at PT Usaha Utama Bersaudara Surabaya, and other partial results. Employee Engagement also has a positive and significant effect on employee performance at PT Usaha Utama Bersaudara Surabaya. Other results also show that Self Efficacy, Self Esteem, and Employee Engagement simultaneously have a positive and significant effect on employee performance at PT Usaha Utama Bersaudara Surabaya.